Perovskite thin film, preparation method thereof and perovskite solar cell
By introducing volatile ion additives to regulate the crystallization direction and speed of perovskites, forming a dense vertical sheet-like structure, solving the problem of poor crystallization quality of thin films in perovskite solar cells and improving photovoltaic conversion efficiency and stability.
Patent Information
- Application Number
- CN202510279766.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-03-11
AI Technical Summary
Among the existing perovskite solar cells, the thin film crystallization quality is poor, resulting in low photovoltaic conversion efficiency and stability.
By introducing volatile ion additives, the crystallization speed of perovskites is delayed and the crystallization direction is regulated. During the first step of annealing, the seed layer is formed and unbonded volatile anions are introduced to form a pore path; during the second step of annealing, the pore path guides the grains to grow vertically, forming a dense and vertical sheet-like structure.
It improves the lattice structure integrity of the perovskite film, reduces the defect state and unpaired bonds at the grain boundaries, improves the mobility and life of carriers, and improves the efficiency and stability of solar cells.
Smart Images

Figure CN119789749A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photovoltaics, and in particular relates to a perovskite film and a preparation method thereof, and a perovskite solar cell. Background Art
[0002] Due to the advantages of low cost and simple process, the research and development of perovskite solar cells (PSCs) has received widespread attention, and the photoelectric conversion efficiency has rapidly increased to a level comparable to that of traditional crystalline silicon solar cells.
[0003] In the structure of PSCs, the perovskite light absorption layer is the key structure for generating photogenerated carriers, and its morphology and crystal quality significantly affect the performance of perovskite solar cells. Given that different components in perovskite materials affect the crystallization process, when the film crystallization quality is poor, the presence of holes inside the perovskite light absorption layer, smaller grain size and excessive grain boundaries will significantly affect the photovoltaic conversion efficiency and stability of the device.
[0004] Therefore, how to obtain a perovskite light absorption layer with fewer defect states and longer carrier lifetime is a key factor in determining the performance of perovskite solar cells. Summary of the invention
[0005] In view of the deficiencies of the prior art, the object of the present invention is to provide a perovskite film and a preparation method thereof and a perovskite solar cell. In the preparation method provided by the present invention, the introduction of volatile ion additives is used to slow down the crystallization speed of perovskite and regulate the crystallization direction of perovskite. During the first step of annealing, the unbonded volatile anions overflow in the form of gas in a very short time while the perovskite seed layer is formed, resulting in the existence of pore passages inside the seed layer. During the second step of annealing, the gas passage guides the vertical orientation growth of the grains, and the vertically oriented grains finally obtained form a dense structure with vertical lamellae. The preparation method helps to fill defects and dislocations in the lattice, improve the integrity of the lattice structure, passivate defect states in the film and unpaired bonds at the grain boundaries, reduce non-radiative recombination, and improve the mobility and life of carriers.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing a perovskite film, the preparation method comprising the following steps:
[0008] The perovskite precursor solution and the volatile ion additive are mixed to obtain a modified perovskite precursor solution.
[0009] The modified perovskite precursor solution is coated on a substrate to form a wet film, and then a first step annealing is performed to form a pore passage perpendicular to the substrate inside the seed layer, and then a second step annealing is performed to allow the crystal to grow along an orientation perpendicular to the substrate to form vertically oriented grains composed of a number of vertical lamellar structures, thereby obtaining the perovskite film; wherein the temperature of the first step annealing is greater than the temperature of the second step annealing, and the holding time of the first step annealing is less than the holding time of the second step annealing.
[0010] In the preparation method provided by the present invention, the introduction of volatile ion additives is used to slow down the crystallization speed of perovskite and regulate the crystallization direction of perovskite. During the first step of annealing, the unbonded volatile anions overflow in the form of gas in a very short time while the perovskite seed layer is formed, resulting in the existence of pore passages inside the seed layer. During the second step of annealing, the gas passages guide the vertical orientation growth of the grains, and the vertically oriented grains finally obtained form a dense structure with vertical lamellae inside. The preparation method helps to fill defects and dislocations in the lattice, improve the integrity of the lattice structure, passivate defect states in the film and unpaired bonds at the grain boundaries, reduce non-radiative recombination, and improve the mobility and life of carriers.
[0011] The structure of the perovskite film obtained by the preparation method provided by the present invention achieves the effects of low defect states and high carrier transfer efficiency, which is beneficial to improving battery efficiency. At the same time, the densely and orderly arranged grains and fewer defect sites are also beneficial to improving battery stability.
[0012] Preferably, the temperature of the first annealing step is greater than the volatilization temperature of the volatile anion in the volatile ion additive.
[0013] Preferably, the temperature of the first annealing step is 180-260°C, for example, it can be 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C or 260°C.
[0014] In the present invention, the appropriate annealing temperature is conducive to the full volatilization of volatile anions, thereby forming tiny pore passages, laying the foundation for the subsequent second-step annealing of crystal orientation growth. If the temperature of the first step annealing is too low, it is not conducive to the rapid formation of pore passages, thereby affecting the preferred orientation growth of grains; if the temperature of the first step annealing is too high, it will lead to irreversible decomposition of the perovskite film and performance collapse.
[0015] Preferably, the holding time of the first annealing step is a first preset time, and the first preset time is the time when the wet film changes from a first color to a second color.
[0016] In the present invention, during the first step of annealing, the temperature is high, so that the solvent in the modified perovskite precursor solution evaporates quickly, and the crystal structure begins to change from disorder to order. This change will change the material's absorption and scattering properties of light, resulting in color changes. When the color change is completed, it indicates that the initial volatilization process of the solvent has been completed and the initial crystal growth has ended. If the holding time of the first step of annealing is too long, that is, the holding time of the first step of annealing is greater than the time for the wet film to change from the first color to the second color, then the continuous high temperature annealing will cause irreversible damage to the perovskite crystal components, affecting the battery performance.
[0017] Exemplarily, the first color is brown-black, and the second color is off-white; it is understandable that the first color and the second color are determined by the composition of the perovskite precursor solution, and are not limited to the specific colors listed in the present invention.
[0018] Preferably, the holding time of the first annealing step is 1-10 s, for example, it can be 1 s, 2 s, 3 s, 4 s, 5 s, 6 s, 7 s, 8 s, 9 s or 10 s.
[0019] In the present invention, under the appropriate holding time, the perovskite precursor material has higher mobility, can more effectively fill the defects and dislocations in the lattice, and improve the integrity of the lattice structure. If the holding time is too long, it will cause negative effects such as decomposition of perovskite film components, morphology degradation and interface failure.
[0020] Preferably, the temperature of the first step annealing is 200-250° C., and the holding time is 2-4 seconds.
[0021] The present invention selects a specific temperature range and holding time, which, in coordination with each other, are conducive to the full volatilization of volatile anions and the formation of tiny pore passages, which not only ensure the integrity of the lattice structure but also lay the foundation for the subsequent preferential orientation growth of grains.
[0022] Preferably, the temperature of the second annealing step is 80-150°C, for example, it can be 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C.
[0023] In the present invention, annealing is performed at a relatively low temperature, which can effectively reduce the thermal stress and defects that may be generated during high-temperature rapid annealing, especially the stress and strain at the interface between perovskite and other layers; it can also reduce overburning and material decomposition caused by high temperature, maintain the integrity of the material, and reduce the loss of electrical properties.
[0024] Preferably, the holding time of the second annealing step is 15-40 min, for example, 15 min, 20 min, 25 min, 30 min or 40 min.
[0025] In the present invention, the appropriate second-step annealing time enables the components in the titanium ore material to gradually migrate and reorganize to form uniform and large-sized grains; the appropriate second-step annealing time also helps to further passivate the defect states in the film and the unpaired bonds at the grain boundaries, reduce non-radiative recombination, and improve the mobility and life of carriers. At the same time, it can also reduce overburning and material decomposition caused by high temperature, maintain the integrity of the material, and reduce the loss of electrical properties.
[0026] Preferably, the temperature of the second annealing step is 90-120° C., and the holding time is 15-30 min.
[0027] The present invention selects a specific temperature range and holding time, and the two work together to not only form uniform and large-sized grains, but also effectively improve the mobility and life of carriers, maintain the integrity of the material, and reduce the loss of electrical properties.
[0028] Preferably, in the volatile ion additive, the volatilization temperature of the volatile anion is ≥100°C, for example, it may be 110°C, 130°C, 150°C, 170°C, 190°C, 200°C, 220°C, 240°C or 260°C.
[0029] Preferably, the volatile anions in the volatile ion additive include any one of formate ions, acetate ions, propionate ions or oxalate ions, or a combination of at least two of them.
[0030] Preferably, the cation in the volatile ion additive includes any one of formamidinium ion, methylamine ion, cesium ion, lead ion or tin ion, or a combination of at least two thereof.
[0031] Preferably, the volatile ionic additive comprises lead acetate.
[0032] Preferably, the molar ratio of the perovskite precursor to the volatile ion additive in the perovskite precursor solution is 1:(0.02-0.1), for example, it can be 1:0.02, 1:0.04, 1:0.06, 1:0.08 or 1:0.1, etc.
[0033] In the present invention, if the molar ratio of the perovskite precursor to the volatile ion additive is too small, that is, the amount of the volatile ion additive added is too much, the excess additive will precipitate, which is not conducive to the formation of a high-quality perovskite film; if the molar ratio of the perovskite precursor to the volatile ion additive is too large, that is, the amount of the volatile ion additive added is too small, it is not conducive to the formation of an effective grain preferential orientation, and the effect of enhancing the crystallization quality of the film grains.
[0034] Preferably, the atmosphere of the low-temperature slow annealing is an air atmosphere.
[0035] Preferably, the relative humidity in the annealing atmosphere of the second annealing step is 20-50%, for example, 20%, 30%, 35%, 40%, 45% or 50%.
[0036] In the present invention, the second step annealing is carried out in an atmosphere with a certain humidity. The trace amount of water vapor in the atmosphere can be used as a morphology regulator in the crystallization process. Through the formation and decomposition of the intermediate phase (such as PbI2·H2O), the crystallization activation energy is reduced, and larger grains and denser films are induced. Since the H2O in the atmosphere is partially dissociated into -OH during annealing, it can react with the uncoordinated Pb 2+ The combination forms Pb-OH bonds, which passivate the surface dangling bonds and improve the stability of the perovskite film.
[0037] Preferably, the preparation method comprises the following steps:
[0038] (1) adding a volatile ion additive to a perovskite precursor solution and mixing the mixture to obtain a modified perovskite precursor solution;
[0039] Among them, the molar ratio of the perovskite precursor and the volatile ion additive in the perovskite precursor solution is 1:(0.02-0.1); the volatile anions in the volatile ion additive include any one of formate ions, acetate ions or oxalate ions or a combination of at least two, and the cations include any one of formamidine ions, methylamine ions, cesium ions, lead ions or tin ions or a combination of at least two.
[0040] (2) coating the perovskite precursor solution on a substrate, and then placing it on a heating table, and performing a first step annealing at a temperature of 180-260° C. in an inert atmosphere, wherein the holding time of the first step annealing is 1-10 seconds, so that the volatile anions are volatilized, thereby forming a pore passage perpendicular to the substrate inside the seed layer, and then cooling to room temperature, and then performing a second step annealing at a temperature of 80-150° C. in an air atmosphere with a relative humidity of 20-50%, wherein the holding time of the second step annealing is 15-40 minutes, so that the grains grow in an orientation perpendicular to the substrate, forming vertically oriented grains with a crystal texture structure, and obtaining the perovskite film.
[0041] In a second aspect, the present invention provides a perovskite film, wherein the perovskite film includes vertically oriented grains, and the vertically oriented grains are composed of a plurality of vertical lamellar structures.
[0042] The vertically oriented grains in the perovskite film provided by the present invention are composed of a number of vertical sheet structures, and the carrier transmission path between the several vertical sheet structures is relatively short, which significantly weakens the scattering effect of the crystal on the carriers, thereby greatly improving the carrier mobility, and because there are fewer grain boundary interfaces, the defect concentration is reduced, resulting in a longer life of electrons in the perovskite film, and a more significant diffusion distance, thereby increasing the chance of long-distance migration of electrons to form current. Therefore, the structure of the perovskite film achieves the effect of low defect state and high carrier transmission efficiency, which is conducive to the improvement of battery efficiency, while the dense and orderly arranged grains and fewer defect sites are also conducive to the improvement of battery stability.
[0043] It should be noted that “several” refers to at least 2, for example 4, 10, 50, 100 or 500, etc.
[0044] It should be noted that "vertically oriented grains" means that the plane where the grains and the perovskite film are located is basically perpendicular, that is, the plane where the grains and the perovskite film are located can be completely vertical, or can be not completely vertical, but slightly inclined to the completely vertical direction.
[0045] Similarly, "several vertical lamellar structures" means that the plane where the lamellar structure is located and the plane where the perovskite film is located are basically perpendicular, that is, the plane where the lamellar structure is located and the plane where the perovskite film is located can be completely perpendicular, or can be incompletely perpendicular and slightly inclined to the completely vertical direction.
[0046] Preferably, the average grain size of the perovskite film is 1-3 μm, for example, 1 μm, 1.5 μm, 2 μm, 2.5 μm or 3 μm.
[0047] The perovskite film provided by the present invention has large-sized vertically oriented grains with a vertical sheet structure, which can provide a smoother transmission path for carriers, reduce the interaction between carriers and grain boundary defects during transmission, and enable carriers to be more efficiently transmitted to electrodes, thereby improving the collection efficiency of carriers and thus improving the photoelectric conversion efficiency of the device. In addition, large-sized grains can make the crystal structure of the perovskite film more complete and orderly, which is conducive to increasing the propagation path length of light in the film and improving the absorption efficiency of light. In addition, under the influence of external environmental factors (such as temperature, humidity, light, etc.), perovskite films with large-sized and dense grains are less prone to structural changes and degradation, and can maintain good performance stability.
[0048] Preferably, the average longitudinal size of the vertically oriented grains is 500-1000 nm, for example, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm or 1000 nm, etc., preferably 700-800 nm.
[0049] In the present invention, the appropriate longitudinal average size can make the combination between grains more compact, improve the overall strength of the material, and effectively reduce the influence of grain boundaries on electron scattering, so that the obstacles to carrier transmission in the material are smaller.
[0050] Preferably, the carrier mobility of the perovskite film is 20-50 cm² / (V·s), for example, it can be 20 cm² / (V·s), 30 cm² / (V·s), 40 cm² / (V·s) or 50 cm² / (V·s), etc.
[0051] The perovskite film provided by the present invention has high carrier mobility and can effectively improve the photoelectric conversion efficiency of the battery.
[0052] Preferably, the chemical formula of the perovskite film is ABX3, wherein A includes any one or a combination of at least two of formamidinium ions, methylamine ions or cesium ions, B includes lead ions and / or tin ions, and X is a halogen ion. For example, it may be FAPbI3, etc.
[0053] In a third aspect, the present invention provides a perovskite solar cell, comprising a stacked substrate, a perovskite film, a first charge transfer layer and an electrode, wherein the perovskite film is prepared by the preparation method described in the first aspect, or is the perovskite film described in the first aspect.
[0054] Preferably, the substrate includes a conductive base and a second charge transport layer stacked in a direction close to the perovskite film.
[0055] Preferably, the first charge transport layer and the second charge transport layer transport charges of opposite electrical properties. For example, the first charge transport layer is an electron transport layer and the second charge transport layer is a hole transport layer, or the first charge transport layer is a hole transport layer and the second charge transport layer is an electron transport layer.
[0056] Preferably, the second charge transport layer is an electron transport layer, and the first charge transport layer is a hole transport layer. Exemplarily, the electron transport layer may be, for example, a SnO2 layer, and the hole transport layer may be, for example, a 2,2',7,7'-tetrakis(N,N-di(4-methoxyphenyl)amino)-9,9'-spirobifluorene (Spiro-OMeTAD) layer.
[0057] Preferably, the thickness of the electron transport layer is 5-15 nm, for example, 5 nm, 8 nm, 10 nm, 12 nm or 15 nm.
[0058] Preferably, the thickness of the hole transport layer is 15-25 nm, for example, 15 nm, 20 nm or 25 nm.
[0059] Preferably, the conductive substrate comprises transparent conductive glass, for example, ITO (indium tin oxide) conductive glass or FTO (fluorine-doped tin oxide) conductive glass.
[0060] Preferably, the thickness of the perovskite film is 500-1000 nm, for example, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm or 1000 nm.
[0061] Preferably, an interface modification layer is further provided between the perovskite film and the first charge transport layer, and the material of the interface modification layer includes any one of PEAI (phenylethylammonium iodide), PDAI (polydopamine), PMMA (polymethyl methacrylate) or NMAI (N-methylacrylimide) or a combination of at least two thereof.
[0062] In the present invention, the function of the interface modification layer is to passivate the upper surface defects of the perovskite film.
[0063] Preferably, the thickness of the interface modification layer is 1-10 nm, for example, 1 nm, 3 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm.
[0064] Preferably, the electrode is made of metal, for example, Ag or Au.
[0065] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0066] Compared with the prior art, the present invention has the following beneficial effects:
[0067] (1) In the preparation method provided by the present invention, the introduction of volatile ion additives is used to slow down the crystallization speed of perovskite and regulate the crystallization direction of perovskite. During the first step of annealing, the unbonded volatile anions overflow in the form of gas in a very short time while the perovskite seed layer is formed, resulting in the existence of pore channels inside the seed layer. During the second step of annealing, the gas channels guide the vertical orientation growth of the grains, and finally the vertically oriented grains are formed with a dense structure with vertical lamellae. This preparation method helps to fill defects and dislocations in the lattice, improve the integrity of the lattice structure, passivate defect states in the film and unpaired bonds at the grain boundaries, reduce non-radiative recombination, and improve the mobility and lifetime of carriers.
[0068] (2) The vertically oriented grains in the perovskite film provided by the present invention are composed of a number of vertical sheet structures, and the carrier transmission path between the vertical sheet structures is relatively short. This preferentially oriented crystal structure weakens its scattering effect on carriers, thereby improving the carrier mobility. In addition, due to the fewer grain boundary interfaces, the defect concentration is reduced, resulting in a longer lifetime of electrons in the perovskite film and a more significant diffusion distance, thereby increasing the chance of long-distance migration of electrons to form current. Therefore, the structure of the perovskite film achieves the effect of low defect states and high carrier transmission efficiency, which is beneficial to the improvement of battery efficiency. At the same time, the densely and orderly arranged grains and fewer defect sites are also beneficial to the improvement of battery stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0069] Figure 1 This is a schematic diagram of the structure of the perovskite solar cell provided in Example 1 of the present invention.
[0070] Figure 2 This is a surface SEM image of the perovskite film provided in Example 1 of the present invention.
[0071] Figure 3 This is a cross-sectional SEM image of a partial structure of a perovskite solar cell provided in Example 1 of the present invention.
[0072] Figure 4 This is a surface SEM image of the perovskite film provided in Comparative Example 1 of the present invention.
[0073] Figure 5 This is a cross-sectional SEM image of a partial structure of a perovskite solar cell provided in Comparative Example 1 of the present invention.
[0074] Among them, 1-high-transmittance glass; 2-FTO layer; 3-electron transport layer; 4-perovskite film; 5-interface modification layer; 6-hole transport layer; 7-Au electrode. DETAILED DESCRIPTION
[0075] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0076] It should be noted that the room temperature below refers to 25°C.
[0077] Example 1
[0078] This embodiment provides a perovskite film, in which crystal grains have a growth orientation perpendicular to a substrate, so that the perovskite film forms a crystal texture structure with a vertical orientation.
[0079] The general chemical formula of the perovskite film is FAPbI3, the average grain size of the perovskite film is 1500nm, and the carrier mobility of the perovskite film is 38cm² / (V·s).
[0080] This embodiment also provides a method for preparing the above perovskite film, the preparation method comprising the following steps:
[0081] (1) Lead acetate is added into a FAPbI3 precursor solution having a concentration of 1.4 mol / L and mixed to obtain a modified perovskite precursor solution.
[0082] Among them, the molar ratio of FAPbI3 precursor and lead acetate is 1:0.06.
[0083] (2) Providing a substrate, the specific steps include:
[0084] The area is 2×2 cm and the resistivity is 7Ω·sq -1 The FTO conductive glass was ultrasonically cleaned in 2% Hellmanex cleaning agent, deionized water, acetone and ethanol for 30 minutes each, dried with clean dry air, and then irradiated in an ultraviolet ozone (UVO) instrument for 15 minutes;
[0085] The diluted SnO2 glue (the SnO2 glue with a volume fraction of 15% was diluted according to SnO2:H2O=1:3) was spin-coated on the FTO conductive glass at a speed of 3000 rpm for 30 seconds, and then annealed at 150°C for 30 minutes to form an electron transport layer.
[0086] Depositing the perovskite film, the specific steps include:
[0087] Take 28 μL of the perovskite precursor solution and drop it on the surface of the electron transport layer of the substrate, spin-coat it at a speed of 4000 rpm for 30 seconds, and add 100 μL of chlorobenzene as an anti-solvent at the 7th second of spin coating. After spin coating, place it on a heating table and perform rapid annealing at a temperature of 250° C. in a nitrogen atmosphere for 5 seconds, so that the acetate ions volatilize, thereby forming a pore passage inside the seed layer, and then cool it to room temperature, and then transfer it to air with a relative humidity of 40%, and perform slow annealing at a temperature of 100° C. for 20 minutes, so that the grains grow along the orientation perpendicular to the substrate, forming a vertically oriented crystal texture structure, and obtaining the perovskite film.
[0088] This embodiment also provides a perovskite solar cell, the structural diagram of which is shown in FIG. Figure 1 As shown, the perovskite solar cell includes a stacked FTO conductive glass, an electron transport layer 3, the perovskite film 4 as described above, an interface modification layer 5, a hole transport layer 6 and an Au electrode 7.
[0089] The FTO conductive glass comprises a stacked high-transmittance glass 1 and a FTO layer 2, wherein the high-transmittance glass 1 has a thickness of 2 mm and a light transmittance of 96%, and the FTO layer 2 has a thickness of 6 nm. The electron transport layer 4 is a SnO2 layer with a thickness of 10 nm. The interface modification layer 5 is a PEAI layer with a thickness of 5 nm. The hole transport layer 6 is a Spiro-OMeTAD layer with a thickness of 20 nm. The Au electrode 7 has a thickness of 100 nm.
[0090] This embodiment also provides a method for preparing the above-mentioned perovskite solar cell, comprising the following steps:
[0091] (a) Using the above-mentioned method for preparing perovskite thin films, a SnO2 layer and a perovskite thin film are sequentially prepared on FTO conductive glass.
[0092] (b) 60 μL of PEAI solution (mass concentration of 10 mg / mL, solvent is isopropanol) was dropped onto the perovskite film and spin coated at 4000 rpm for 30 s to form a PEAI layer.
[0093] (c) 20 μL of the Spiro-OMeTAD solution was dropped onto the PEAI layer and spin coated at 4000 rpm for 40 s to form a Spiro-OMeTAD layer.
[0094] (d) A layer of Au electrode is deposited on the outer surface of the Spiro-OMeTAD layer by vacuum evaporation.
[0095] Figure 2The surface SEM image of the perovskite film provided in Example 1 is shown. It can be seen from the figure that the grains in the perovskite film provided by the present invention have a crystal texture structure (multiple strip structures substantially parallel to each other) inside, which means that the part of the grains in the perovskite film close to the surface of the perovskite film is a plurality of sheet structures. Further, Figure 3 The cross-sectional SEM image of the partial structure of the perovskite solar cell provided in Example 1 is shown. In the image, the perovskite film 4 includes a plurality of vertical texture structures, indicating that not only the part of the grains in the perovskite film 4 close to the surface of the perovskite film 4 is a sheet structure, but also the inside of the grains is a vertical sheet structure; at the same time, it also shows that the grains of the perovskite film are also vertically oriented. Therefore, combined with Figure 2 and Figure 3 It can be shown that the structure of the perovskite film provided by the present invention includes vertically oriented grains, and the vertically oriented grains are composed of a number of vertical lamellar structures. This structure achieves the effects of low defect states and high carrier transfer efficiency, which is beneficial to improving battery efficiency. At the same time, the densely and orderly arranged grains and fewer defect sites are also beneficial to improving battery stability.
[0096] Example 2
[0097] The difference between this embodiment and embodiment 1 is that the molar ratio of the FAPbI3 precursor to lead acetate is 1:0.02.
[0098] The average grain size of the perovskite film provided in this embodiment is 900 nm, and the carrier mobility is 25 cm² / (V·s).
[0099] The rest of the preparation methods and parameters were the same as those in Example 1.
[0100] Example 3
[0101] The difference between this embodiment and embodiment 1 is that the molar ratio of the FAPbI3 precursor to lead acetate is 1:0.04.
[0102] The average grain size of the perovskite film provided in this embodiment is 1200 nm, and the carrier mobility is 33 cm² / (V·s).
[0103] The rest of the preparation methods and parameters were the same as those in Example 1.
[0104] Example 4
[0105] The difference between this embodiment and embodiment 1 is that the molar ratio of the FAPbI3 precursor to lead acetate is 1:0.1.
[0106] The average grain size of the perovskite film provided in this embodiment is 1800nm, and the carrier mobility is 30cm² / (V·s).
[0107] The rest of the preparation methods and parameters were the same as those in Example 1.
[0108] Example 5
[0109] The difference between this embodiment and embodiment 1 is that lead acetate is replaced by lead formate.
[0110] The average grain size of the perovskite film provided in this embodiment is 1400nm, and the carrier mobility is 35cm² / (V·s).
[0111] The rest of the preparation methods and parameters were the same as those in Example 1.
[0112] Example 6
[0113] The difference between this embodiment and embodiment 1 is that lead acetate is replaced by lead oxalate.
[0114] The average grain size of the perovskite film provided in this embodiment is 1450nm, and the carrier mobility is 33cm² / (V·s).
[0115] The rest of the preparation methods and parameters were the same as those in Example 1.
[0116] Example 7
[0117] The difference between this embodiment and embodiment 1 is that in the step of depositing the perovskite film, the temperature of the rapid annealing is 180° C., the temperature of the slow annealing is 80° C., and the time of the slow annealing is 25 min.
[0118] The average grain size of the perovskite film provided in this embodiment is 1300nm, and the carrier mobility is 30cm² / (V·s).
[0119] The rest of the preparation methods and parameters were the same as those in Example 1.
[0120] Example 8
[0121] The difference between this embodiment and embodiment 1 is that in the step of depositing the perovskite film, the rapid annealing temperature is 220° C., the rapid annealing time is 3 s, the slow annealing temperature is 150° C., and the slow annealing time is 15 min.
[0122] The average grain size of the perovskite film provided in this embodiment is 1400nm, and the carrier mobility is 33cm² / (V·s).
[0123] The rest of the preparation methods and parameters were the same as those in Example 1.
[0124] Example 9
[0125] The difference between this embodiment and embodiment 1 is that the molar ratio of the FAPbI3 precursor to lead acetate is 1:0.01.
[0126] The rest of the preparation methods and parameters were the same as those in Example 1.
[0127] Example 10
[0128] The difference between this embodiment and embodiment 1 is that the molar ratio of the FAPbI3 precursor to lead acetate is 1:0.15.
[0129] The rest of the preparation methods and parameters were the same as those in Example 1.
[0130] Embodiment 11
[0131] The difference between this embodiment and embodiment 1 is that in the step of depositing the perovskite film, the temperature of the rapid annealing is 150°C.
[0132] The rest of the preparation methods and parameters were the same as those in Example 1.
[0133] Example 12
[0134] The difference between this embodiment and embodiment 1 is that in the step of depositing the perovskite film, the temperature of the rapid annealing is 280°C.
[0135] The rest of the preparation methods and parameters were the same as those in Example 1.
[0136] Example 13
[0137] The difference between this embodiment and embodiment 1 is that in the step of depositing the perovskite film, the rapid annealing time is 8 seconds.
[0138] The rest of the preparation methods and parameters were the same as those in Example 1.
[0139] Embodiment 14
[0140] The difference between this embodiment and embodiment 1 is that in the step of depositing the perovskite film, the temperature of the slow annealing is 70°C.
[0141] The rest of the preparation methods and parameters were the same as those in Example 1.
[0142] Embodiment 15
[0143] The difference between this embodiment and embodiment 1 is that in the step of depositing the perovskite film, the temperature of the slow annealing is 160°C.
[0144] The rest of the preparation methods and parameters were the same as those in Example 1.
[0145] Comparative Example 1
[0146] The difference between this comparative example and Example 1 is that step (1) is not performed, that is, lead acetate is not introduced into the APbI3 precursor solution.
[0147] The rest of the preparation methods and parameters were the same as those in Example 1.
[0148] Figure 4 and Figure 5 The surface SEM image and cross-sectional SEM image of the perovskite film provided in this comparative example are respectively shown. It can be seen from the figures that the grains of the perovskite film provided in this comparative example have no crystal texture structure and do not show a lamellar structure.
[0149] Performance Testing
[0150] The photoelectric performance and stability of the perovskite solar cells provided in the above embodiments and comparative examples were tested.
[0151] Photoelectric performance test conditions: AM1.5, 1000W / m 2 , 25±2℃.
[0152] Stability test conditions: Perform a 1000-hour stability test on the battery in an air environment (relative humidity is 20-40%), and record the ratio of the battery efficiency after 1000 hours to the original efficiency.
[0153] The test results are shown in Table 1.
[0154] Table 1
[0155]
[0156] analyze:
[0157] As can be seen from the above table, the present invention uses the introduction of volatile ion additives to slow down the crystallization rate of perovskite and regulate the crystallization direction of perovskite. During the high-temperature rapid annealing process, the unbonded volatile anions overflow in the form of gas in a very short time while forming the perovskite seed layer, resulting in the existence of pore passages inside the seed layer. During the low-temperature slow annealing process, the gas passages guide the vertical orientation growth of the grains, and finally form a dense structure with vertical texture. The structure of the perovskite film prepared based on this preparation method achieves the effect of low defect state and high carrier transfer efficiency, which is beneficial to the improvement of battery efficiency. At the same time, the dense and orderly arranged grains and fewer defect sites are also beneficial to the improvement of battery stability.
[0158] It can be seen from Examples 1 and 9-10 that if the molar ratio of the FAPbI3 precursor to lead acetate is too small, that is, the amount of lead acetate added is too much, it is not conducive to improving the battery efficiency and stability; if the molar ratio of the FAPbI3 precursor to lead acetate is too large, that is, the amount of lead acetate added is too little, it will not have a significant effect on improving the battery efficiency and stability.
[0159] It can be seen from Examples 1 and 11-12 that if the rapid annealing temperature is too low, the preferential orientation growth of the perovskite film grains will be affected, which is not conducive to the transport of carriers; if the rapid annealing temperature is too high, it will cause the decomposition of some components, which is not conducive to the stability of the crystal structure.
[0160] It can be seen from Example 1 and Example 13 that if the rapid annealing time is too long, it will be detrimental to the crystallization of the perovskite film grains, and if the high temperature time is too long, it will cause the decomposition of the components, thereby affecting the electrical properties.
[0161] It can be seen from Examples 1 and 14-15 that if the slow annealing temperature is too low, the perovskite grains will not be fully crystallized, the defect state will increase, and the overall performance will deteriorate; if the slow annealing temperature is too high, the overheated grains will be thermally decomposed, causing irreversible effects on stability.
[0162] It can be seen from Example 1 and Comparative Example 1 that the introduction of volatile ion additives can improve the crystallization quality of the perovskite film, and the interface between the perovskite film and the charge transport layer is free of holes, which increases the carrier extraction capacity and extraction rate, so that the efficiency and stability of the obtained battery are significantly improved.
[0163] The present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a perovskite film, characterized in that: The preparation method comprises the following steps: mixing a perovskite precursor solution and a volatile ion additive to obtain a modified perovskite precursor solution; The modified perovskite precursor solution is coated on a substrate to form a wet film, and then a first step annealing is performed to form a pore passage perpendicular to the substrate inside the seed layer, and then a second step annealing is performed to allow the crystal to grow along an orientation perpendicular to the substrate to form vertically oriented grains composed of a number of vertical lamellar structures, thereby obtaining the perovskite film; wherein the temperature of the first step annealing is greater than the temperature of the second step annealing, and the holding time of the first step annealing is less than the holding time of the second step annealing.
2. The method for preparing a perovskite thin film according to claim 1, characterized in that: The temperature of the first step annealing is greater than the volatilization temperature of the volatile anion in the volatile ion additive; And / or, the temperature of the first step annealing is 180-260°C; And / or, the holding time of the first annealing step is a first preset time, and the first preset time is the time for the wet film to change from the first color to the second color; And / or, the holding time of the first step annealing is 1-10s; And / or, the temperature of the first step annealing is 200-250° C., and the holding time is 2-4 seconds.
3. The method for preparing a perovskite thin film according to claim 1, characterized in that: The temperature of the second step annealing is 80-150°C; And / or, the holding time of the second step annealing is 15-40min; And / or, the temperature of the second annealing step is 90-120° C., and the insulation time is 15-30 min.
4. The method for preparing a perovskite thin film according to claim 1, characterized in that: The volatile anions in the volatile ion additive include any one of formate ions, acetate ions, propionate ions or oxalate ions, or a combination of at least two thereof; And / or, the cation in the volatile ion additive includes any one of formamidinium ion, methylamine ion, cesium ion, lead ion or tin ion, or a combination of at least two thereof.
5. The method for preparing a perovskite thin film according to claim 1, characterized in that: The molar ratio of the perovskite precursor to the volatile ion additive in the perovskite precursor solution is 1:(0.02-0.1); And / or, the relative humidity in the annealing atmosphere of the second annealing step is 20-50%.
6. The method for preparing a perovskite thin film according to claim 1, characterized in that: The preparation method comprises the following steps: (1) adding a volatile ion additive to a perovskite precursor solution and mixing the mixture to obtain a modified perovskite precursor solution; Wherein, the molar ratio of the perovskite precursor in the perovskite precursor solution to the volatile ion additive is 1:(0.02-0.1); the volatile anions in the volatile ion additive include any one or a combination of at least two of volatile ionic acidic solutions such as formate ions, acetate ions, propionate ions or oxalate ions, and the cations include any one or a combination of at least two of formamidinium ions, methylamine ions, cesium ions, lead ions or tin ions; (2) coating the perovskite precursor solution on a substrate, and then placing it on a heating table, and performing a first step annealing at a temperature of 180-260° C. in an inert atmosphere, wherein the holding time of the first step annealing is 1-10 seconds, so that the volatile anions are volatilized, thereby forming a pore passage perpendicular to the substrate inside the seed layer, and then cooling to room temperature, and then performing a second step annealing at a temperature of 80-150° C. in an air atmosphere with a relative humidity of 20-50%, wherein the holding time of the second step annealing is 15-40 minutes, so that the grains grow in an orientation perpendicular to the substrate, forming vertically oriented grains with a crystal texture structure, and obtaining the perovskite film.
7. A perovskite film, characterized in that: The perovskite film includes vertically oriented grains, and the vertically oriented grains are composed of a plurality of vertical sheet structures.
8. The perovskite film according to claim 7, characterized in that: The average grain size of the perovskite film is 1-3 μm; and / or, the vertically oriented grains have an average longitudinal size of 500-1000 nm; And / or, the carrier mobility of the perovskite film is 20-50cm² / (V·s).
9. A perovskite solar cell, characterized in that: The perovskite solar cell comprises a stacked substrate, a perovskite film, a first charge transport layer and an electrode. The perovskite film is prepared by the method for preparing a perovskite film according to any one of claims 1 to 6, or is the perovskite film according to claim 7 or 8.
10. The perovskite solar cell according to claim 9, characterized in that: The substrate includes a conductive base and a second charge transport layer stacked in a direction close to the perovskite film; And / or, the first charge transport layer and the second charge transport layer transport charges of opposite electrical properties; And / or, the thickness of the perovskite film is 500-1000 nm; And / or, an interface modification layer is further provided between the perovskite film and the first charge transport layer, and the material of the interface modification layer includes any one of PEAI, PDAI, PMMA or NMAI or a combination of at least two thereof; And / or, the thickness of the interface modification layer is 1-10 nm.
Citation Information
Patent Citations
Confined-range annealing method and preparation method of perovskite thin film or solar cell
CN115312667A
Perovskite thin film, preparation method thereof and perovskite solar cell
CN116193957A
Perovskite precursor solution, perovskite solar cell and preparation method
CN118678861A
Perovskite film prepared by coating method and application thereof
CN118890945A
Annealing device for assisting vertical orientation crystallization of perovskite film
CN220044091U